Comics Versus Art - Beaty, Bart (University of Toronto Press, 2022)
On the surface, the relationship between comics and the 'high' arts once seemed simple; comic books and strips could be mined for inspiration, but were not themselves considered legitimate art objects. Though this traditional distinction has begun to erode, the worlds of comics and art continue to occupy vastly different social spaces.Comics Versus Art examines the relationship between comics and the most important institutions of the art world, including museums, auction houses, and the art press. Bart Beaty's analysis centres around two questions: why were comics excluded from the history of art for most of the twentieth century, and what does it mean that comics production is now more closely aligned with the art world? Approaching this relationship for the first time through the lens of the sociology of culture, Beaty advances a completely novel approach to the comics form